Self-Regulated Learning: Implementation of Equality Educa-tion During The Covid-19 - Sardin, Sardin; Banyu Biru, Rembulan Catra; Rosmia, Ade Romi (Journal of Nonformal Education, 2022)
Covid-19 conditions that have an impact on the education sector, especially on the non-formal education pathway through the equality education program at the Community Learning Activity Center (PKBM) located in the West Bandung Regency Region. Since this pandemic, the government has made a policy that initially face-to-face learning will switch to an online learning environment. This study aims to describe self-regulated learning strategies and learning outcomes in the Package C equivalence education program during the pandemic. The population is 2469 people studying Package C class 12 in West Bandung Regency and the research sample is 304 people. Data was obtained by distributing questionnaires through Google Form for one month. The statistical method used is quantitative descriptive analysis. The research findings show that: The picture of the learning strategy that emerged is Self-regulated learning, where students proactively acquire academic skills, such as setting goals, strategies for sorting and moving the learning process independently by setting study schedules, setting learning targets and seeking required information. independently. Learning Outcomes in the Package C Equivalence Program during the Pandemic Period are shown by the attitude of wanting to learn, willingness to work on new assignments, being cooperative in-class activities, being consistent in doing assignments, and accepting corrections if they are not as desired.